(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2019)
Four fish species namely, stinging catfish (Heteropneustes fossilis), spotted snakehead (Channa punctatus), climbing perch (Anabas testudineus) and tangra (Batasio tengana) were exposed to various concentrations of chlorpyrifos (Expert 20 EC) to investigate the mortality rate of fish species and the toxicity level of the pesticide. The LC50 values of chlorpyrifos on these fish species were 23.10, 20.32, 16.61 and 13.94 ppm, respectively at 96 hours of exposure. Among these results, it is clear that the lethal concentration is varying species to species because their strengths are different. During the experiments, some water quality parameters such as temperature, pH, dissolved oxygen, total dissolved solids and electrical conductivity were also analyzed. The temperature values remained within the ranges of 17-20°C and the pH was 6.64-7.30. Fish behaved irregular and erratic movements followed by hyper excitability, loss of balance and settling to the bottom of the test chamber. At higher concentration of chlorpyrifos, alterations in physiological and behavioural responses especially erratic swimming, gulping, mucus secretion, increased opercular movement and profuse emission of mucus all above the body were observed during the primary stages of contact after which it became occasional. Int. J. Agril. Res. Innov. & Tech. 9 (1): 42-47, June, 2019